Multiple criteria decision analysis with consideration to place-specific values in participatory forest planning - Nordström, Eva-Maria; Eriksson, Ljusk Ola; Karin, Öhman (2011)
The combination of multiple criteria decision analysis (MCDA) and participatory planning is an approach that has been applied in complex planning situations where multiple criteria of very different natures are considered, and several stakeholders or social groups are involved. The spatial character of forest planning problems adds further to the complexity, because a large number of forest stands are to be assigned different treatments at different points in time. In addition, experience from participatory forest planning indicates that stakeholders may think about the forest in terms of place-specific values rather than in forest-wide terms. The objective of this study was to present an approach for including place-specific values in MCDA-based participatory forest planning and illustrate the approach by a case study where the objective was to choose a multipurpose forest plan for an area of urban forest in northern Sweden. Stakeholder values were identified in interviews, and maps were used to capture place-specific spatial values. The nonspatial and nonplace-specific spatial values were formulated as criteria and used to build an objective hierarchy describing the decision situation. The place-specific spatial values were included in the creation of a map showing zones of different silvicultural management classes, which was used as the basis for creation of forest plan alternatives in the subsequent process. The approach seemed to work well for capturing place-specific values, and the study indicates that formalized methods for including and evaluating place-specific values in participatory forest planning processes should be developed and tested further.